Environmentally-certified space and retail revenues: A study of U.S. bank branches. (20th February 2019) - Chang, Qingqing; Devine, Avis
Abstract: Much research exists measuring income and valuation premiums to owners and operators of environmentally-certified real estate, yet little work examines the financial impact to the space users, outside of decreased utility costs. Such implications for space users are of great importance, as tenant businesses may be unwilling or unable to pay a rental rate premium for environmentally-certified space if there is not an associated user benefit. Under a simple yet rigorous fixed effects model with geographic clustering, we study the relationship between environmentally-certified retail space and location-specific financial performance. Examining retail bank branches, we find that LEED certified spaces are associated with above average deposit levels, while Energy Star-certified branches offer inconsistent results. These results are tested in an event study which validates the findings, and indicates that the benefits of LEED extend years past initial certification, evidencing lasting income-related benefits. Finally, bank- and branch-specific subsample analyses confirm these results while controlling for idiosyncratic characteristics. Highlights: Environmentally-certified retail space experiences higher retail revenues. LEED-certified space performs better than Energy Star-certified space. Findings persist over time, in varied programs, and under stringent modeling. Higher green outlet retail revenues justify green rent premiums. Financially viable premiums allow for proliferation of sustainable real estate.